Structural response of concrete-filled round-ended stub columns subjected to eccentric loads. (1st April 2019) - Piquer, A.; Ibañez, C.; Hernández-Figueirido, D.
Highlights: Tests on eccentrically loaded stub concrete-filled round-ended steel columns. Different load eccentricities and concrete grades as infill are employed. Influence of concrete infill, composite action and ductility are studied. An equivalent rectangular concrete-filled tubular section approach is presented. Provisions of Eurocode 4 are assessed and compared to experimental data. Abstract: In this paper, the results of an experimental campaign on 9 concrete-filled round-ended steel tubular (CFRT) stub beam-columns subjected to eccentric loads are presented. Different levels of load eccentricity were considered including reference specimens subjected to concentric loads. In order to study the effect of the concrete infill strength in the ultimate capacity, two types of concrete infill were employed: normal and high strength concrete. In view of the experimental results, the dependency of the type of response on the load eccentricity and strength of concrete infill of the beam-columns was analysed. In addition to the effect of the concrete infill, the result of the composite action and the level of ductility were also studied by means of different parameters. It was found that the cross-sectional capacity is inversely proportional to the load eccentricity and that, in addition, it is highly sensitive to the region within the cross-section where the load application point lies. The experimental ultimate loads of the specimens were compared with the corresponding failure loads given by Eurocode 4 as well as with the combined axial force-bending moment interaction curve. In this case, the comparison showed that for high load eccentricities, code predictions are too conservative. Finally, an approach based on an equivalent rectangular CFST cross-section is presented and applied to calculate the capacity of tested columns, obtaining accurate predictions.